Hubungan Antara Kelancaran Pengeluaran Asi Dengan Kejadian Postpartum Blues Di Wilayah Puskesmas Trucuk II 8 Klaten - Idha Suparwati; Murwati Murwati; Endang Suwanti (Poltekkes Kemenkes Surakarta, 2018)
Abstract: The smoothness of Breastfeeding, Post Partum Blues Occurrence. The incompleteness of breast milk (ASI) is one of the problems when the mother begins to breastfeed her baby. If not addressed immediately will result in anxiety and anxiety about the mother's ability to breastfeed. If this condition is left it will continue to be post partum blues and even postpartum depression. The purpose of this study was to determine the relationship between the smoothness of breastfeeding expenditure and postpartum blues incidence in the Trucuk II Klaten district. This research design is analytical descriptive research with cross sectional approach. The sample is normal postpartum day 3-10 at Trucuk II Klaten Health Center in May 2017 as many as 48 people, by purposive sampling. Analysis of univariate and bivariate data with chi square test correlation. Maternal breastfeeding expenditure was 93.8% in the current category. Post partum blues events were 44.2%. Statistic test results obtained p value = 0.001. There is a relationship between the smooth expenditure of breast milk with Postpartum Blues Occurrence in Trucuk II Klaten District Health Center.